Utilization of Information Technology-Based Management Accounting to Optimize Export-Oriented Business Strategies - Ardhya Nanggala; Santoso; Yona Eka Pratiwi; Alif Farhan Romadhani; Fadel Madeng (Journal of Social and Community Service, 2026)
This community service program was implemented at the school-based SME unit of Saiburi Chaengpracakarn School, Sai Buri District, Pattani Province, Thailand, during the 07 – 15 September 2025. It was designed to enhance the understanding and managerial capacity of 25 teachers who manage the school's export-oriented SME unit in applying information technology-based management accounting to support the formulation of business strategy. The partners' main problems comprised limited capacity in preparing cost information, weak managerial control, and the absence of accurate, data-driven strategic decision-making. The program was implemented through a 9-hour intensive one-day training session, followed by intensive mentoring, and the simple adoption of an IT-based management accounting system using Microsoft Excel and Google Sheets. Using a researcher-developed instrument (three 10-item multiple-choice tests, one per construct, scored on a 0-100 scale) administered to all 25 participants, a Wilcoxon signed-rank test showed statistically significant post-training gains across all three assessed competencies: management accounting concepts (40.0 to 80.0; p = .021), IT-based cost recording (36.0 to 78.0; p = .010), and export pricing simulation (32.0 to 85.0; p = .015).